ANALISIS PELAKSANAAN PENGELUARAN BIAYA APBDesa DALAM MENUNJANG PEMBANGUNAN DESA - Ersantiana Kue Wea; Any Rustia Dewi (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2019)
The purpose of this study is to analyze and determine how the role of government in Village management Village Budget Financing in Supporting Rural Development in Kupang Regency. This study uses qualitative data analysis methods that are presented in descriptive narrative with data education techniques, data presentation and conclusion drawing. The role of the village government in managing the income budget and expenditure management in supporting rural development funding is fully functioning properly because there are no obscure budgets or incomplete data, the condition of the village and village regulatory systems is only informal but with all the village officials working equally well to seek implementation of the Village Budget with transparent and participatory financial accountability.